If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 + -8t = 5 + -9t Solving 16 + -8t = 5 + -9t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '9t' to each side of the equation. 16 + -8t + 9t = 5 + -9t + 9t Combine like terms: -8t + 9t = 1t 16 + 1t = 5 + -9t + 9t Combine like terms: -9t + 9t = 0 16 + 1t = 5 + 0 16 + 1t = 5 Add '-16' to each side of the equation. 16 + -16 + 1t = 5 + -16 Combine like terms: 16 + -16 = 0 0 + 1t = 5 + -16 1t = 5 + -16 Combine like terms: 5 + -16 = -11 1t = -11 Divide each side by '1'. t = -11 Simplifying t = -11
| 0.75x+3.22=6.97 | | 1x+4=7x-3 | | 2(x+4)-3=4x-2(-5+x) | | 112-4x=4x-24 | | y+5(y-1)=7 | | (5x-2)(2x)=115 | | -43-2x=17-8x | | 7p+1=5p+25 | | 10=5+2x | | 24x^2+36=4x*h | | 2(c-1)=4(3-c) | | 4x^2+36x=4x*h | | 6x+29x-7=7(5x+4) | | 3y+9=2y-6 | | 6x^2-7x+3=0 | | 3r+8=3 | | 3(2-x)=x+2 | | 4x+36x=4x*h | | 5q-5=17 | | 2(3n-1)=(4n+8)+7 | | 2.00-.33=.22x | | 2t+6=21-t | | 5(5x+2)-9=25x+1 | | 8c=90-c | | 11-5y=4y+20 | | 65-5x=4x+23 | | 47x+1673x-15=43(40x+60) | | 11+5y=4y+20 | | 4(t+2)=18-t | | x^2+3x-2x=5x+1 | | .6x-4.2=.6 | | 93-5x=8x-15 |